Sequential Form Formation Diagrams in Architectural Design - Ozdemir, Berk; Onal, Feride (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
This article discusses approaches to architectural design and the use of diagrams as a design tool, including specifications for the development process and methods of use of diagrams, and evaluates this approach that is both flexible and subjective. Interpretations of information and data analysis using diagrammatic methods and their effects on creation of architectural form are examined. Based on theoretical foundation established in the initial section of the report, the second half analyzes research regarding sequential form formation diagrams, examining their content and potential. The question, Is it a design tool or just a simple presentation technique? was considered with regard to diagrams submitted for architectural competitions based on diagrammatic strategies and the effects on the city and users. Using these considerations for the sample projects, a formal, functional and conceptual classification was created to analyze such diagrams and design steps.
Keywords: Conceptual diagrams; diagram; diagram architecture; sequential form formation diagrams; Architecture